2011
DOI: 10.1007/s10499-011-9467-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of ammonia on juvenile cobia (Rachycentron canadum, Linnaeus, 1766) according to the salinity

Abstract: Juvenile cobia (Rachycentron canadum) (total length 15.16 ± 0.92 cm and weight 19.26 ± 4.5 g) were exposed to different concentrations of ammonia-N (unionized plus ionized ammonia as nitrogen), using the static renewal method at different salinity levels of 5, 20, and 35% at pH 8.1 and 25°C. The 24, 48, 72, 96 h LC 50 values of ammonia-N for R. canadum juveniles were 60.mg l -1 at 5%, respectively. The 24, 48, 72, 96 h LC 50 values of NH 3 -N (unionized ammonia as nitrogen) were 1.81, 1.46, 1.12, and 0.68 mg l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 46 publications
1
9
0
9
Order By: Relevance
“…147,148 . Além disso, o acúmulo de contaminantes no sedimento pode se expressar biologicamente sob a forma de toxicidade e/ou alteração na estrutura da comunidade bentônica.…”
Section: Contaminação Química E Efeitos Tóxicos Sobre As Comunidades unclassified
See 1 more Smart Citation
“…147,148 . Além disso, o acúmulo de contaminantes no sedimento pode se expressar biologicamente sob a forma de toxicidade e/ou alteração na estrutura da comunidade bentônica.…”
Section: Contaminação Química E Efeitos Tóxicos Sobre As Comunidades unclassified
“…Alguns países europeus e estados norte-americanos hoje em dia já exigem o tratamento secundário para permitir o lançamento de efluentes 14,148 . Além disso, como as zonas costeiras concentram outras fontes de poluentes, devem ser realizados estudos contínuos e monitoramentos visando avaliar os efeitos cumulativos e sinérgicos do conjunto de fontes ali implantadas.…”
Section: Recomendaçõesunclassified
“…Despite the existence of many studies on different fish species concerning acute ammonia toxicity (WEIRICH and RICHE, 2006a;WEIRICH and RICHE, 2006b;COSTA et al, 2008;BARBIERI and DOI, 2012;RODRIGUES et al, 2014), no studies were found on the effects of ammonia exposure on sardine species.…”
Section: Introductionmentioning
confidence: 99%
“…Os metais pesados há tempos têm sido reconhecidos como contaminantes ambientais, podendo, de acordo com a concentração, provocar graves problemas de saúde pública e ambientais 1,2,3,4,5,6,7 . No Brasil, os metais pesados entram nos ecossistemas aquáticos por descargas de efluentes industriais que são liberados direta ou indiretamente no ambiente 6,7 .…”
Section: Introductionunclassified
“…No Brasil, os metais pesados entram nos ecossistemas aquáticos por descargas de efluentes industriais que são liberados direta ou indiretamente no ambiente 6,7 . Altas concentrações de metais pesados têm sido registradas em águas costeiras 5,8 , rios e estuários 9 , em crustáceos 10,11 e em tecidos de vertebrados marinhos 12,13,14 .…”
Section: Introductionunclassified